USING GUIDING QUESTIONS TO PROMOTE STUDENTS' CRITICAL THINKING - Supratman, Eman (2015)
Critical thinking is the ability that can be promoted through the explicit and direct teaching of four basic language skills. It is also said that questions lead to the act of thinking. However, teaching critical thinking through reading is still the case for junior high school students because this skill hasn't been nurtured when they were in elementary school. The study was an attempt to explore classroom practice and collect empirical evidence that allowed reasonable conclusions regarding the influence of the implementation of Guiding Questions in teaching reading on both learning process and outcomes dealing with the development of students' critical thinking skills as well as students' perceptions towards it. A qualitative case study design was employed, involving fifteen eight graders of a Junior Secondary School in Majalengka. This study was descriptive interpretive in nature since it described the phenomena under investigation in participants' point of views and interpreted what they perceived concerning the topic at hand. Qualitative and quantitative data were collected through classroom observations, semi-structured interview and achievement tests. The qualitative data were analyzed against five dimensions of learning (Marzano, 1992) and critical thinking theories proposed by some experts in terms of classroom climate, classroom tasks and activities, students' attitudes and their progress in critical thinking skills and dispositions. The test results were calculated in terms of their mean scores and compared to each other in order to find out the progress. The findings reveal that the implementation of guiding questions in reading instructions could to a certain extent promote students' critical thinking skills. The critical thinking test results indicated the increasing mean scores. The average of students' scores in the pre-test was 3.6. They made a one-point increase in the mid test (4.6) and a 0.4 point (5) in the post test. The findings also show that students responded positively towards classroom climate and tasks. It was indicated by the increasing number of participating students from lesson to lesson. Students' active engagements in classroom activities increased from only 53,33% (8 out of 15 students) in the first three meetings; 80% (12 out of 15 students) in the fourth, fifth, sixth and seventh meetings; until 86,67% (13 out of 15) students in the eighth and last meeting. KEY WORDS: Critical Thinking, Critical Reading, Guiding Questions Berpikir kritis adalah kemampuan yang dapat dikembangkan melalui pengajaran eksplisit dan langsung empat keterampilan dasar bahasa. Dikatakan bahwa pertanyaan dapat mengarahkan proses berpikir. Namun, mengajar berpikir kritis melalui membaca kepada siswa SMP masih sulit dilakukan karena keterampilan ini belum dikembangkan ketika mereka belajar di sekolah dasar. Penelitian ini merupakan upaya untuk mengeksplorasi praktek pembelajaran dan mengumpulkan bukti-bukti empiris yang memungkinkan untuk menarik kesimpulan yang wajar mengenai pengaruh penerapan Pertanyaan Penuntun baik terhadap proses maupun hasil pembelajaran membaca terkait dengan perkembangan keterampilan berpikir kritis serta persepsi siswa terhadap pembelajaran itu. Sebuah desain studi kasus kualitatif diterapkan, dengan melibatkan 15 orang siswa kelas VIII sebuah sekolah menengah pertama di Majalengka. Penelitian ini adalah penelitian deskriptif interpretatif karena menggambarkan fenomena yang diselidiki dalam sudut pandang partisipan dan persepsi mereka tentang topic penelitia. Baik data kualitatif maupun kuantitatif dikumpulkan melalui observasi kelas, wawancara semi-terstruktur dan tes prestasi. Data kualitatif dianalisis dengan dimensi belajar (Marzano, 1992) dan teori-teori pemikiran kritis yang diajukan oleh beberapa ahli terkait suasana kelas, tugas-tugas dan kegiatan pembelajaran, sikap siswa dan kemajuan keterampilan serta disposisi berpikir kritis mereka. Nilai rata-rata hasil tes dihitung dan dibandingkan satu sama lain untuk mengetahui kemajuan mereka. Hasil penelitian menunjukkan bahwa penerapan pertanyaan penuntun dalam pembelajaran membaca, sampai batas tertentu, bisa meningkatkan keterampilan berpikir kritis siswa. Hasil tes berpikir kritis menunjukkan nilai rata-rata yan meningkat. Rata-rata skor siswa dalam pre-test adalah 3,6. Mereka membuat kenaikan satu poin pada tes yang dilakukan pada pertengahan penelitian (4,6) dan 0,4 poin (5) dalam tes akhir. Temuan penelitian juga menunjukkan bahwa siswa merespon positif suasana kelas dan tugas-tugas pembelajaran. Hal ini ditunjukkan dengan meningkatnya jumlah peserta siswa dari pertemuan ke pertemuan. Keterlibatan siswa secara aktif dalam kegiatan kelas meningkat dari hanya 53,33% (8 dari 15 siswa) di tiga pertemuan pertama; 80% (12 dari 15 siswa) pada pertemuan keempat kelima, keenam dan ketujuh; sampai 86,67% (13 dari 15) siswa dalam pertemuan kedelapan dan pertemuan terakhir. KATA KUNCI: berpikir kritis, membaca kritis, Membimbing Pertanyaan